Lisch Nodules in Neurofibromatosis Type 1 - J Gordon Millichap (Pediatric Neurology Briefs)
The prevalence of Lisch nodules among 167 patients with neurofibromatosis 1 is reported from the Department of Pediatrics, Genetics Division, Miami Children’s Hospital, Miama, FL.